1996
DOI: 10.1111/j.1474-8673.1996.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DQ‐2511 on neutral activity in afferent and efferent loops of gastric vagovagal reflex pathways in the rat

Abstract: 1. DQ-2511 is a new substituted benzamide compound that has gastric prokinetic properties. Actions of the drug on neural discharge in the innervation of the stomach of anaesthetized rats were studied. Standard extracellular methods of multi-unit recording were used to study rates of firing in afferent and efferent filaments teased from gastric branches of the vague nerve. 2. Decreased firing in gastric vagal efferents was associated with increased rates of discharge in the gastric afferents. 3. Intravenous app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…The facilitation of gastric emptying involves the sensory component of gastric inhibitory vago-vagal reflex circuits [5,7,13]. The data were supported by the fact that the enhancement of the efferent discharge provoked by ecabapide was completely blocked by bilateral vagotomy.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The facilitation of gastric emptying involves the sensory component of gastric inhibitory vago-vagal reflex circuits [5,7,13]. The data were supported by the fact that the enhancement of the efferent discharge provoked by ecabapide was completely blocked by bilateral vagotomy.…”
supporting
confidence: 63%
“…The data were supported by the fact that the enhancement of the efferent discharge provoked by ecabapide was completely blocked by bilateral vagotomy. Furthermore, pretreatment with ecabapide completely inhibited the actions of cholecystokinin-octapeptide (CCK8), which suppressed activity in the gastric efferents and simultaneously elevated discharge rates in the afferent nerves [13]. On the other hand, ecabapide was reported to be free of anticholinesterase property and to be devoid of adverse effects including the prolactin release or extrapyramidal reactions [8,9] common to antidopaminergic agents [2,16].…”
mentioning
confidence: 99%
“…Electro physiological approaches revealed that the drug elicited a facilitatory effect on the gastric efferent activity as a result of a disinhibitory reflex action originating from sup pressed gastric afferents (4). Although the binding affinity of ecabapide to selective receptors has been exhaustively explored, it showed no specific binding (2,5).…”
mentioning
confidence: 99%
“…Although the binding affinity of ecabapide to selective receptors has been exhaustively explored, it showed no specific binding (2,5). On the ba sis of the above studies, ecabapide was considered to exert its action via suppression of activation of afferents in the sensory component of gastric inhibitory vago-vagal reflex pathways (3,4). More recently, ecabapide was reported to stimulate the intracellular production of guanosine 3",5' cyclic monophosphate (cGMP) content (5,6) at a con centration as low as 10-' M when rabbit gastric parietal cells were used (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation